Body contouring in adolescents following bariatric surgery - Derderian, S Christopher (Surg Obes Relat Dis, 2019)
BACKGROUND: Bariatric surgery leads to sustained weight loss and resolution of obesity-associated comorbidities in severely obese adolescents. However, one consequence of massive weight loss is excess skin and soft tissue. Many details regarding the timing, outcomes, and barriers associated with body contouring surgery (BCS) in youth who have undergone bariatric surgery are unknown. METHODS: Teen-Longitudinal Assessment of Bariatric Surgery (Teen-LABS) is a prospective multi-institutional study of 242 adolescents who underwent bariatric surgery from 2007 to 2012. Utilization of BCS was analyzed in this population with comparison of anthropometrics and excess skin-related symptoms between those who did and those who did not undergo BCS. RESULTS: Among the 198 study participants with BCS data available, 25 (12.6%) underwent 41 body contouring procedures after bariatric surgery. The most common BCS was panniculectomy (n=23). Presence of pannus-related symptoms at baseline and the magnitude of weight loss within the first year after bariatric surgery were independently associated with subsequent panniculectomy (p=0.04 and p=0.03, respectively). All adolescents who underwent panniculectomy experienced resolution of pannus-related symptoms. At five years after bariatric surgery, 74% of those who did not undergo panniculectomy reported an interest in the procedure and 58% indicated that cost/insurance coverage was the barrier to obtaining BCS. CONCLUSION: Few adolescents who underwent bariatric surgery later underwent BCS procedures. Panniculectomy effectively treated pannus-related symptoms. Disparities in access to surgical care for adolescents who desire BCS warrants further investigation.